ANALYSIS OF STUDENT'S LEARNING INTEREST IN COOPERATIVE LEARNING MODEL IN LEARNING ART OF PAINTING AT SMA NEGERI 3 PADANG - sindy claudia; Zubaidah Zubaidah (Universitas Negeri Padang, 2022)
This study aims to analyze students' interest in learning in the cooperative learning model in painting learning at SMA Negeri 3 Padang. This study uses a descriptive qualitative research method. The subjects in this study were 30 students of class X at SMA Negeri 3 Padang. The result of this research is that students' interest in learning in the cooperative learning model of painting at SMA Negeri 3 Padang has a percentage of 72.9%, which means that it belongs to the high category and is of interest to some students. The conclusion that the researcher draws from this study is that students' interest in learning in the cooperative learning model in painting learning can be achieved in class X students' interest in learning at SMA Negeri 3 Padang.